2007
DOI: 10.1007/s11420-006-9030-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Determinations by Dual-Energy x-ray Absorptiometry in the Management of Patients with Marfan Syndrome—Some Factors Which Affect the Measurement

Abstract: Reduced bone mineral density (BMD) was sporadically reported in patients with Marfan syndrome. This may or may not place the Marfan patient at increased risk for bone fracture. In comparing the BMDs of our patients with those reported in the literature, it seemed that agreement between values, and hence the degree of osteoporosis or osteopenia reported, was dependent on the instrumentation used. The objective of this study was to statistically assess this impression. Bone mineral density measurements from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…26,27 The etiology of this bone loss remains speculative, but no significant increase in bone fracture rates has been seen. 28 …”
Section: Skeletalmentioning
confidence: 99%
“…26,27 The etiology of this bone loss remains speculative, but no significant increase in bone fracture rates has been seen. 28 …”
Section: Skeletalmentioning
confidence: 99%
“…Marfan syndrome is an autosomal-dominant disorder that affects fibrillin-1, a glycoprotein that provides structural support in elastin [40]. The abnormalities in fibrillin-1 result in abnormalities of the cardiovascular, ocular, and musculoskeletal system.…”
Section: The Effect Of Collagen Disorders On Bone Qualitymentioning
confidence: 99%
“…Common skeletal findings include idiopathic scoliosis, lumbosacral dural ectasia, acetabular protrusion, and ligamentous laxity [41]. Patients with Marfan syndrome are also reported to have reduced BMD [40,66]. The decrease in BMD is equally present in both genders and is more pronounced at predominantly cortical sites [66].…”
Section: The Effect Of Collagen Disorders On Bone Qualitymentioning
confidence: 99%
“…A comparison of the measures observed in the study by Giampietro et al [7] and those of other published studies which employed either the Lunar DPX or Hologic QDR 1000 W dual-energy X-ray absorptiometry (DXA) bone densitometers to assess BMD in patients with Marfan syndrome was performed to assess whether differences in BMD could be related to the instrumentation used [6,9,11,13]. Results of these analyses are summarized in Tables 1 and 2 and show some instances of discrepancy which could be attributed to the instrumentation utilized [15]. Significantly higher differences in spinal BMD in both men and women were observed in Giampietro's study [15] compared to those reported by Carter et al [6] BMD values of the femoral neck in men were higher in the Giampietro study [15] than those reported by both Le Parc et al [11] and Carter et al [6] but closer to the control values reported by Le Parc (see Table 1) [11].…”
Section: Marfan Syndromementioning
confidence: 99%
“…Results of these analyses are summarized in Tables 1 and 2 and show some instances of discrepancy which could be attributed to the instrumentation utilized [15]. Significantly higher differences in spinal BMD in both men and women were observed in Giampietro's study [15] compared to those reported by Carter et al [6] BMD values of the femoral neck in men were higher in the Giampietro study [15] than those reported by both Le Parc et al [11] and Carter et al [6] but closer to the control values reported by Le Parc (see Table 1) [11].…”
Section: Marfan Syndromementioning
confidence: 99%